The INFLUENCE OF FINANCIAL LITERACY AND THE USE OF SOCIAL MEDIA ON PERSONAL FINANCIAL MANAGEMENT IN STUDENTS OF THE MANAGEMENT STUDY PROGRAM, FACULTY OF ECONOMICS AND BUSINESS, JAMBI UNIVERSITY - Putra, Ruli Amanda; Setiawati, Rike; Firmansyah, Firmansyah (Management Department, Faculty of Economics and Business, Universitas Jambi, 2024)
Understanding financial literacy is very necessary for every individual to be able to manage and plan their finances. Based on the results of observations, researchers found problems related to low levels of financial literacy affecting their financial management. Of the 10 students, only 4 students made financial plans and only a few made detailed financial plans. In particular, they have studied Financial Management courses but are known to still be unable to apply their financial literacy skills appropriately in managing their finances. This research aims to examine the influence of financial literacy and the use of social media on student financial management. This research includes quantitative research methods. The population in this study was 577 students from the Faculty of Economics and Business, Jambi University class 2019-2021 with a sample of 86 students using simple random sampling techniques. Data collection was carried out through distributing questionnaires. Data testing techniques use Validity Test and Reliability Test, R-Square test and Hypothesis Test with Bootstrapping using SmartPLS 3 Software. The results of the research show that financial literacy has a significant positive effect on personal financial management and the use of social media has a significant positive effect on personal financial management.